Chain wear and elongation in elite cycling: a case study - Aubert, R.; Grappe, F.; Roizard, X.; Vincent, T.; Lallemand, F. (Journal of Science and Cycling, 2023)
In modern cycling, chain drives are commonly used since they are reliable and very efficient (1). However, their efficiency is known to be a function of chain wear, being highest after a few break-in kilometres and then slightly decreasing with the accumulated kilometres (2). Bicycle mechanics usually use mechanical gauges in order to check the chain elongation and therefore decide when to replace the chain. However, chain elongation can result from both material loss due to friction and mechanical elongation caused by a plastic deformation of the chain elements, which would be independent of material loss. Moreover, the wear of chain link elements is not uniform (3). The aim of this study is to determine the part of plastic deformation on chain elongation. The hypothesis is that plastic deformation is highly responsible for chain elongation. Identical chain spans were tested either on fatigue on a traction machine or in real riding conditions, on a same number of chain cycles (150 000). Since the traction machine acts only in the longitudinal axle, there is no friction occurring during these tests which therefore cause mechanical elongation but no wear. On the other hand, real riding conditions combine both traction and friction. Chain spans elongation was measured throughout the tests. For real riding conditions, parameters such as power output (W), pedalling cadence (rpm), gear ratio, weather and lubrication were controlled. They allowed to determine the chain tension Fn (N), the number of chain cycles and the mechanical work W endured by the chain roller (Nm).